(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This aims to determine the effect of target practice on shooting accuracy in extracurricular soccer at SDN Parakanmuncang II. The research method used is Quantitative with the Research Design used, namely One Group Pretest-Posttest Design, one group will be given a Pretest before being given Treatment and Posttest after being given Treatment, the Sample used is Random Sampling. Data was collected using a shooting test into the goal. The results of data analysis show the normality test Pretest sig value 0.189> 0.05 while the Posttest value is 0.441> 0.05, it can be concluded that the Pretest-Posttest data has a normal distribution. The Homogeneity Test shows 0.804> 0.05, so the Pretest and Posttest data are Homogeneous. Hypothesis testing using the Paired Sample t-Test Test with a sig value (2-tailed) shows a result of 0.001